PENGARUH PENGGUNAAN MEDIA BANGKU TERHADAP HASIL BELAJAR KAYANG PESERTA DIDIK SMAN 1 SEKADAU HILIR - Nadi, Agus; Triansyah, Andika; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is how the influence of bench media usage on learning result backbend learnes SMAN 1 Sekadau Hilir. The purpose of research to determine the influence of bench media on learning result backbend on student SMAN 1 Sekadau Hilir. Experimental research method, with pre-experimental design. Study population, all students of class X SMAN 1 Sekadau Hilir amounted to 158 people. Samples using purposive sampling technique took 32 student. Data analysis using t-test analysis. The results of research and data analysis obtained the average initial test 4,34 and the average final test 6,47 (increased by 2,13). Based on analysis of influence test, withdrawal of hypothesis of t-hitung value that is equal to 16 by looking at statistic table where at degress of freedom dk=(n-i) is 32-1=31 and at significant level 5% abtained t-table value of 2,03961. Hence the value of t-hitung 16 is greater than t-table=2,03961 it means that the accepted hypothesis means that there is influence of bench media usage on the learning backbend on the students SMAN 1 Sekadau Hilir. While the percentage of enchancement is 49,08%. Based on the result can be concluded that there is influence of bench media usage on learning result backbend. Keywords: Bench Media, Learning Result Backbend.